PERBANDINGAN AKTIVITAS ANTIOKSIDAN JAHE EMPRIT (Zingiber officinale var Amarum) DAN JAHE MERAH (Zingiber officinale var Rubrum) DALAM SEDIAAN CAIR BERBASIS BAWANG PUTIH DAN KORELASINYA DENGAN KADAR FENOL DAN VITAMIN C - Ike Yulia Wiendarlina; Runi Sukaesih (Jurnal Fitofarmaka Indonesia, 2019)
Garlic (Allium sativum L.), ginger emprit (Zingiber officinale var Amarum) and red ginger (Zingiber officinale var Rubrum) contain active compounds from the phenol group which have antioxidant properties. This study aims to determine the ratio of antioxidant activity of red ginger and ginger in garlic-based liquid preparations using DPPH reagent (1.1 diphenyl-2 picrylhydrazyl) and determine its correlation with total phenol and vitamin C levels contained in both liquid preparations. Total phenol content was determined by reacting folin-ciocalteu and vitamin C levels were determined by titrimetric method. Total phenol levels are expressed as mg GAE (Gallic Acid Equivalent) per gram of preparation, antioxidant activity is expressed as IC50 (µg / mL), and vitamin C is expressed as percent (%). The results show that total phenol content of emprit and red ginger in garlic-based preparation were 80,296 mgGAE / g preparations and 159,164 mgGAE / g preparations respectively, antioxidant activity (IC50) for each preparation were 3,310 µg / mL and 2,075 µg / mL respectively and the vitamin C level were 4.338% and 6.372%. Correlation test showed the very strong and significant correlation existed between antioxidant activity and the total phenol levels in both emprit and red ginger-garlic preparation but no significant correlation detected between antioxidant activity and vitamin C levels of both preparations.